2019
DOI: 10.1167/iovs.19-27334
|View full text |Cite
|
Sign up to set email alerts
|

Steeper Macular Curvature in Eyes With Non-Highly Myopic Retinitis Pigmentosa

Abstract: PURPOSE. A posterior staphyloma has been reported to be present in some eyes with retinitis pigmentosa (RP), and the purpose of this study was to determine the macular curvature of non-highly myopic RP eyes. METHODS. This was a retrospective, observational study. The medical charts of the right eyes of 143 patients with RP and 60 controls whose axial length ranged from 21.5 mm to 26.0 mm were reviewed. The mean curvature of Bruch's membrane within 6 mm of the central macula obtained from the horizontal optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…In an earlier study, we found a nonlinear relationship between the EZ width and the MMCI; the MMCI was lower in eyes with an EZ width of around 2200 µm, and the MMCI was higher in eyes with shorter or longer EZ widths. 10 Thus, we divided the eyes into three groups according to the EZ width at the baseline; >2000 µm (mild, 42 eyes), between 0 and 2000 µm (moderate, 42 eyes), and no EZ (severe, 23 eyes). Only the mild group had a significant change in the MMCI during the experimental period ( P = 0.011, one-sample t -test).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an earlier study, we found a nonlinear relationship between the EZ width and the MMCI; the MMCI was lower in eyes with an EZ width of around 2200 µm, and the MMCI was higher in eyes with shorter or longer EZ widths. 10 Thus, we divided the eyes into three groups according to the EZ width at the baseline; >2000 µm (mild, 42 eyes), between 0 and 2000 µm (moderate, 42 eyes), and no EZ (severe, 23 eyes). Only the mild group had a significant change in the MMCI during the experimental period ( P = 0.011, one-sample t -test).…”
Section: Resultsmentioning
confidence: 99%
“…The methods to measure the macular curvature in the SD-OCT images have been described in detail. 10 Briefly, each horizontal and vertical SD-OCT image was corrected for the difference in the pixel resolution in the transverse and longitudinal directions. Then, the reflective line corresponding to Bruch's membrane across the fovea (yellow line in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MNUinduced photoreceptor degeneration is rapidly progressing, while RP is a relatively chronic retinopathy with a much longer course. 1,36 Therefore, the progression rate should be considered as an instinctive disadvantage of the MNU-induced models, as it deviates somewhat from the natural history of human RP.…”
Section: Discussionmentioning
confidence: 99%